SARS-CoV-2 Infection in Cancer Patients: A Population-Based Study - Zorzi, Manuel; Guzzinati, Stefano; Avossa, Francesco; Fedeli, Ugo; Calcinotto, Arianna; Rugge, Massimo (Frontiers in Oncology, 2021)
Aim Few population-based studies focus on the risk and outcomes of SARS-CoV-2 infection considering only cancer patients. This retrospective population-based study investigates the outcome(s) of SARS-CoV-2 infection in patients whose cancer was diagnosed within 10 years before testing for the virus. Methods Malignancies were distinguished as incident or prevalent (active or inactive) cases. Cancer management and vital status were retrieved from institutional databases. Comorbidities were recorded, based on Adjusted Clinical Groups. Six Resource Utilization Bands (RUBs) were also considered. Independent risk factors for SARS-CoV-2 infection and death were identified using multivariable stepwise logistic regression, considering sex, age, comorbidities and RUBs, cancer status, cancer site, and treatments. Results Among 34929 cancer patients, 1090 (3·1%) tested CoV2+ve. The risk of infection was associated with age (OR per 1-year increase=1·013; 95%CI=1·008-1·017), prevalent-inactive disease, hematologic malignancies (OR=1·36; 95%CI=1·05-1·76) and RUB (OR per 1-level increase=1·15; 95%CI=1·07-1·24). The risk of death was twice as high for males, and increased with age (OR per 1-year increase=1·07; 95%CI=1·06-1·09) and comorbidities (renal [OR=2·19; 95%CI=1·15-4·28], respiratory [OR=2·06; 95%CI=1·26-3·39]). Only lung malignancies raised the mortality risk (OR=3·63; 95%CI=1·61-8·41). Among CoV2+ve cancer patients, incident or prevalent-active disease, lung malignancy (OR=3·63; 95%CI=1·61-8·41), and recent chemotherapy (OR=2·12; 95%CI=1·28-3·54) increased the risk of death. Conclusion In a large cohort of cancer patients, the risk of SARS-CoV-2 infection was higher for those with inactive disease than in incident or prevalent-active cases. Among CoV2+ve cancer patients, active cancer and recent chemotherapy both significantly raised the risk of death, which increased particularly for lung cancer.